KAJIAN LITERATUR ORIENTASI POLYCHRONIC DALAM HUBUNGANNYA DENGAN KEPUASAN KERJA, KEADILAN DISTRIBUTIF SERTA KEINGINAN BERPINDAH KERJA - Setiawati, Herning; Supartha, Wayan Gede; Subudi, Made (Buletin Studi Ekonomi; VOL.22.NO.2. AGUSTUS 2017 (PP 113-261), 2017)
Purpose of this review is to explore research about polychronic orientation. Polychronic orientation is the tendency of a person’s behavior in completing many tasks or jobs in one period of time. Results of the review note that there is still growing discussion on definition of polychronic orientation. Discussions appear to whether this orientation is an individual or cultural domain. There were still ambiguous distinction between polychronic orientation and multitasking behavior. Search also found that there is still a lack of research and study that examines the polychronic orientation on collaboration in a group or team. The review also revealed that there were inconsistencies on findings of polychronicity orientation effect on performance. Polychronic orientation should be placed as part of a person environtment-fit theory in explaining the effect on performance and the various aspects of the organization. This review found there are still shortage research about the effect of polychronic orientation on job satisfaction, distributive fairness and turnover intention. This topic should be considering in further research. Keywords: polychronic orientation, polychronicity, person job-fit, job satisfaction, distributive fairness, turnover intention.